New perspectives on Ezra-Nehemiah history and historiography, text, literature, and interpretation - Kalimi, Isaac 1952- (Winina Lake, Ind Eisenbrauns, 2012)
Pt. 1. History and historiography -- pt. 2. Text, literature, and interpretation
Includes bibliographical references and index. - Description based on print version record
Online-Ausg.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc -- Bible -- Bible; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible. Ezra -- Criticism, interpretation, etc -- Criticism, interpretation, etc; Bible. Nehemiah -- Criticism, interpretation, etc -- Criticism, interpretation, etc; Bible; RELIGION ; Biblical Studies ; Old Testament; Religion; Philosophy & Religion; Judaism; Criticism, interpretation, etc; Electronic books; Electronic books -- Criticism, interpretation, etc